Impact of tenofovir disoproxil fumarate on bone metabolism and bone mass among perinatally HIV-infected Asian adolescents - Tavitiya Sudjaritruk (2018)
© 2017 International Medical Press. Background: This study aimed to determine the effect of tenofovir disoproxil fumarate (TDF) on bone metabolism and bone mass in HIV-infected adolescents. Methods: This was a sub-study of a cross-sectional multicentre bone health trial that enrolled perinatally HIV-infected Thai and Indonesian adolescents (10–18 years) with viral suppression on antiretroviral therapy. Participants were classified into two groups as TDF users and non-users. Bone metabolism-related markers (25-hydroxyvitamin D [25-OHD], intact parathyroid hormone [iPTH], bone turnover biomarkers), and lumbar spine dual-energy X-ray absorptiometry were assessed. Bone mineral density (BMD)/bone mineral apparent density (BMAD) Z-scores were calculated. Results: Of 394 adolescents, 136 (34.5%) and 258 (65.5%) were TDF users and non-users, respectively. Among TDF users, median age (IQR) was 16.1 (14.7–17.4) years and TDF treatment duration (IQR) was 2.3 (1.4–3.1) years. Among TDF non-users, median age (IQR) was 14.3 (12.6–16.4) years. BMD and BMAD Z-scores comparing TDF users with non-users were -0.8 and -0.6 (P=0.27), and -0.3 and -0.2 (P=0.58), respectively. The association between TDF use and iPTH elevation was intensified in adolescents with suboptimal vitamin D levels (25-OHD <30 ng/ml; P=0.001). TDF administration was positively associated with bone resorption marker (P=0.04) and negatively associated with bone formation marker (P=0.04). With data up to 4 years, neither association between TDF use and bone mass loss (BMD: P=0.09; BMAD: P=0.22), nor variation of bone mass Z-scores by TDF treatment duration (BMD: P=0.34; BMAD: P=0.58) was demonstrated. Conclusions: Recent TDF administration was correlated with PTH elevation and bone turnover dysregulation but not with bone mass reduction in our cohort. A study with extended follow-up to ascertain TDF-associated bone mass deterioration is warranted.